1971
DOI: 10.3758/bf03208951
|View full text |Cite
|
Sign up to set email alerts
|

The latencies of correct and incorrect responses in discrimination and detection tasks: Their interpretation in terms of a model based on simple counting

Abstract: A model for two-choice discrimination based on a process of simple counting is described, and two experiments are performed to test the predictions of the model concerning the graph of latency as a function of response proportion. Two main forms of this graph are identified and predicted to arise in different circumstances. The experimental results support the model, and its possible extension to other psychophysical situations, especially signal detection, are then discussed. It is compared with a model deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Specifically, according to the semantic coding view, as previously stated, stimulus-code translation occurs after the discrimination is performed. Although the discrimination time for errors is typically longer than for correct responses when conditions emphasize accuracy (see, e.g., Petrusic & Jamieson, 1989;Pike, 1971), the code translation component, which accounts for the congruity effect, is supposedly a constant time increment. Moreover, since errors can also occur as a consequence of the failure to translate codes and thereby reduce the semantic congruity effect's magnitude, the overall congruity effect for error responses cannot be larger than for correct responses.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, according to the semantic coding view, as previously stated, stimulus-code translation occurs after the discrimination is performed. Although the discrimination time for errors is typically longer than for correct responses when conditions emphasize accuracy (see, e.g., Petrusic & Jamieson, 1989;Pike, 1971), the code translation component, which accounts for the congruity effect, is supposedly a constant time increment. Moreover, since errors can also occur as a consequence of the failure to translate codes and thereby reduce the semantic congruity effect's magnitude, the overall congruity effect for error responses cannot be larger than for correct responses.…”
Section: Methodsmentioning
confidence: 99%
“….05], confirming an RT difficulty effect under accuracy stress but not under speed stress. Finally, the interaction between group and correct and error RTs was reliable [F(1,8) = 20.17, p < .003] because, as is typically the case in psychophysical comparison tasks, error times were longer than correct times under accuracy stress but were approximately equal to correct times under speed stress (for reviews, see Luce, 1986;Petrusic, 1992;Pike, 1968Pike, , 1971Vickers, 1979).…”
Section: Accuracy Speedmentioning
confidence: 99%
“…First, Murdock and Dufty (1972) showed that, contrary to empirical results, strength theory predicts smaller RT variability for errors than for correct responses. Second, strength theory predicts that error RTs will always be longer than correct RTs (e.g., Coombs, 1964;Petrusic & Jamieson, 1978;Pike, 1973;Vickers, 1979), a prediction which is easily disconfirmed under conditions emphasizing speeded responding (e.g., Experiment 1) where error RTs are typically either the same as or faster than correct RTs (see Luce, 1986;Petrusic, 1992;Pike, 1971;Vickers, 1979).…”
Section: Decision Times and Calibration Theorymentioning
confidence: 99%
“…Independent accumulator models accumulate information pertaining to the corresponding alternative with zero consultation of other accumulation occurring in the decision process (Brown & Heathcote, 2008;LaBerge, 1962;Merkle & Van Zandt, 2006;Pike, 1971;Rouder, Province, Morey, Gomez, & Heathcote, 2015;Vickers, 1970). Importantly, as illustrated in the right panel of Figure 1, the evidence accumulation process of one accumulator does not explicitly depend on the state of the other accumulator.…”
Section: Extant Theories About Evidence Accumulationmentioning
confidence: 99%